2017
DOI: 10.1016/j.cogdev.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Complex spatial language improves from 3 to 5 years: The role of prompting and overhearing in facilitating direction giving using Between and Middle

Abstract: McInnis, M. S. (2017). Complex spatial language improves from 3 to 5 years: The role of prompting and overhearing in facilitating direction giving using between and middle. for help with data collection, transcription, and coding. We also thank the parents and children for their participation and area preschools for their support. Hund, A. M., Bianchi, L. J., Winner, J. F., & Hesson-McInnis, M. S. (2017). Complex spatial language improves from 3 to 5 years: The role of prompting and overhearing in facilitating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Tolins et al (2017) found that children learned novel words better from people participating in a naturalistic conversation (e.g., “That’s a dax.” “You’re right, that is a dax.”) than when people spoke without responding directly to one another (e.g., “That’s a dax” said by the first adult followed by a nonverbal acknowledgment, such as a nod, from a second adult). Furthermore, Foster and Hund (2012) and Hund et al (2017) employed a different methodology to test children’s language learning from overhearing. Instead of asking children to match an item with a word, they required children to spontaneously produce words overheard from adult dyads.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Tolins et al (2017) found that children learned novel words better from people participating in a naturalistic conversation (e.g., “That’s a dax.” “You’re right, that is a dax.”) than when people spoke without responding directly to one another (e.g., “That’s a dax” said by the first adult followed by a nonverbal acknowledgment, such as a nod, from a second adult). Furthermore, Foster and Hund (2012) and Hund et al (2017) employed a different methodology to test children’s language learning from overhearing. Instead of asking children to match an item with a word, they required children to spontaneously produce words overheard from adult dyads.…”
Section: Resultsmentioning
confidence: 99%
“…This group of articles shows that the kinds of objective information that children learn from overhearing are not limited to novel words and facts. Although not ubiquitous, children can spontaneously reproduce some of what they overhear (Foster & Hund, 2012; Hund et al, 2017) and apply it to a novel situation (Mills et al, 2012). Furthermore, children recall complex information like directions (Foster & Hund, 2012; Hund et al, 2017; Mills et al, 2012) and narrative events (Tsethlikai & Rogoff, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations